The phylogeny of leaf beetles (Chrysomelidae) inferred from mitochondrial genomes. (2nd September 2019) - Nie, Rui‐e; Andújar, Carmelo; Gómez‐Rodríguez, Carola; Bai, Ming; Xue, Huai‐Jun; Tang, Min; Yang, Chen‐Tao; Tang, Pu; Yang, Xing‐Ke; Vogler, Alfried P.
Abstract: The high‐level classification of Chrysomelidae (leaf beetles) currently recognizes 12 or 13 well‐established subfamilies, but the phylogenetic relationships among them remain ambiguous. Full mitochondrial genomes were newly generated for 27 taxa and combined with existing GenBank data to provide a dataset of 108 mitochondrial genomes covering all subfamilies. Phylogenetic analysis under maximum likelihood and Bayesian inference recovered the monophyly of all subfamilies, except that Timarcha was split from Chrysomelinae in some analyses. Three previously recognized major clades of Chrysomelidae were broadly supported: the 'chrysomeline' clade consisting of (Chrysomelinae (Galerucinae + Alticinae)); the 'sagrine' clade with internal relationships of ((Bruchinae + Sagrinae) + (Criocerinae + Donaciinae)), and the 'eumolpine' clade comprising (Spilopyrinae (Cassidinae (Eumolpinae (Cryptocephalinae + Lamprosomatinae)))). Relationships among these clades differed between data treatments and phylogenetic algorithms, and were complicated by two additional deep lineages, Timarcha and Synetinae. Various topological tests favoured the PhyloBayes software as the preferred inference method, resulting in the arrangement of (chrysomelines (eumolpines + sagrines)), with Timarcha placed as sister to the chrysomeline clade and Synetinae as a deep lineage splitting near the base. Whereas mitogenomes provide a solid framework for the phylogeny of Chrysomelidae, the basal relationships do not agree with the topology of existing molecular studies and remain one of the most difficult problems of Chrysomelidae phylogenetics. Abstract : Full mitochondrial genomes were newly generated for 27 taxa and combined with existing GenBank data to provide a dataset of 108 mitochondrial genomes covering all subfamilies. Phylogenetic inference recovered the monophyly of all subfamilies, except that Timarcha was split from Chrysomelinae in some analyses. Three previously recognized major clades of Chrysomelidae were broadly supported. The mitogenomes provide a solid framework for the phylogeny of Chrysomelidae.